Pengaruh Machiavellian, Kecerdasan Spiritual Terhadap Perilaku Etis Apip Dengan Budaya Organisasi Sebagai Variabel Mediasi (Studi Kasus Pada Inspektorat Kota Bukittinggi) - Fauzan, Ahmad; Yulihasri, Yulihasri (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The Inspectorate is one of the public sector local government organizations that aims to monitor and observe what is actually happening and compare it with what should have happened. If it turns out that there are deviations or obstacles, it is hoped that they can be immediately identified, so that corrective action can be taken immediately. Through this corrective action, it is hoped that the implementation of the activities concerned can still achieve its objectives to the fullest. The research subjects were employees of the Bukittinggi City Inspectorate. A sample of 35 employees was determined using the proportionate stratified random sampling technique. This type of research is quantitative research. Data collection techniques using a questionnaire with a Likert scale model of 5 alternative answers. Data analysis was performed using SEM (Structural Equation Modeling) analysis which was operated based on Partial Least Square (PLS) with two independent variables, one dependent variable and one mediating variable. This study results that machiavellian nature has a negative effect on ethical behavior with organizational culture as a mediating variable, while spiritual intelligence has a positive effect on ethical behavior with organizational culture as a mediating variable at the Inspectorate of Bukittinggi City.